Alta Mills, Harvey County - Peters, Grant (Kansas State University, The Chapman Center for Rural Studies, 2013)
This study is about the small Alta Mills community in Alta Township, Harvey County, Kansas, and the history of how it came to be. The long journey and migration of Mennonites to Kansas and the cooperative rural spirit they brought made Alta Mills the community center it was. Included are maps, photographs, and interviews.
Grant Peters, “Alta Mills, Harvey County,” Chapman Center Research Collections,https://ccrsresearchcollections.omeka.net/items/show/116..
Keywords: Alta Mills; Turkey Red wheat; Harvey County; Buhler Burrton; Joseph Schrag; Stucky family